2019
DOI: 10.22159/ajpcr.2019.v12i18.34218
|View full text |Cite
|
Sign up to set email alerts
|

Protective of Ethanolic Extract of Saussurea Lappa Against Paracetamol-Induced Hepatic and Renal Damage in Male Rabbits

Abstract: Objective: The objective of our study is to investigate the effect of the ethanolic extract of Saussurea lappa against paracetamol-induced hepatorenal toxicity in male rabbits. Methods: Eighteen male rabbits were used for this study and were divided into three groups of six rabbits each. Group 1: Rabbits were the normal (negative control), Group 2: (Positive control) Rabbits were administered paracetamol at dose 300 mg/kg body weight (B.W) for 14 day, and Group 3: Rabbits received paracetamol at dose 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
4
1
0
Order By: Relevance
“…Initially, the erythrogram and leukogram components were not significantly altered in the S. lappa ethanolic-extract-treated group except for notable leukocytosis and lymphocytosis. A comparable hemogram was previously reported following S. lappa oral administration in rats [56] and rabbits [57]. The increment of lymphocyte count is usually associated with the enhancement of murine immunological function [58].…”
Section: Discussionsupporting
confidence: 82%
“…Initially, the erythrogram and leukogram components were not significantly altered in the S. lappa ethanolic-extract-treated group except for notable leukocytosis and lymphocytosis. A comparable hemogram was previously reported following S. lappa oral administration in rats [56] and rabbits [57]. The increment of lymphocyte count is usually associated with the enhancement of murine immunological function [58].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, liver tissue of GIII and GIV rats improved greatly, as shown by current histological examination compared to GII. The results of our current study agree with [30]. In a recent study, it was found that the extract of the S.lappa root can protect the liver from the toxic effect of CCL 4 [31].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with [35,36]. This might be because phytochemical components including flavonoids, and chlorogenic acid function as antioxidants, reducing PTU toxicity by decreasing free radical-induced lipid peroxidation [30,37].…”
Section: Discussionsupporting
confidence: 85%
“…The same results obtained by Saad et al, (2018) who reported that oral administration of an aqueous extract of Indian costus significantly increased body weights when compared to the control group, also, Kadhem (2019) showed a significant increase (P≤0.05) in final LBW and BWG of rabbits treated with the ethanolic extract of Saussurea lappa compared to the control group, through its contents which were flavonoids, proteins, and carbohydrates, which are necessary for growth, body repair, and maintenance.…”
Section: Effect Of Sle On Growth Performancesupporting
confidence: 79%